Francis Ford Coppola - Menne, Jeff, 1974- (Contemporary film directors., 2014)
Acclaimed as one of the most influential and innovative American directors, Francis Ford Coppola is also lionised as a maverick auteur at war with Hollywood's power structure and an ardent critic of the postindustrial corporate America it reflects. However, Jeff Menne argues that Coppola exemplifies the new breed of creative corporate person and sees the director's oeuvre as vital for reimagining the corporation in the transformation of Hollywood.